Promoting Culture and Tourism in Nigeria Through Calabar Festival and Carnival Calabar - Andrew, Esekong H.; Ekpenyong, Ibok (Mediterranean Journal of Social Sciences, 2012)
This Paper examines current measures of cultural promotion and tourism development in Nigeria, focusing on the efforts ofCross River State. Described as Nigeria’s foremost tourists’ destination, Cross River State has developed what appears to be a uniquecultural and tourism development plan, featuring two major products – The Calabar Festival and Carnival Calabar in its tourism calendar.In the first place, the paper analyses the structures and dimensions of the two cultural and tourism products, situating them in thecontexts of traditionality and modernity on the one hand, and globalization and localization on the other. In the later part, the paperattempts to evaluate the economic, social and political implications of the festival and carnival on tourism development in Nigeria. Inconclusion, the paper affirms that with products such as Calabar Festival and Carnival Calabar, Nigeria may already have started theprocess of economic diversification from oil driven economy to ecological/cultural tourism-driven economy of the future.Recommendations are made towards the fortification of the tourism industry, particularly in the areas of security and privatization foraccelerated growth.